Giant Hemangioma of the Urinary Bladder: A Case Report - Chowdhury, Mohammad Golam Mowla; Akter, Nasima; Hassan, Md Sajid; Shameem, Isteaq Ahmed; Morshed, Mohammad Selim (Bangladesh Journal of Urology, 2020)
Abstract Not Available Bangladesh Journal of Urology, Vol. 18, No. 1, Jan 2015 p.40-42